Atlas of Brazilian Snakes: Verified Point-Locality Maps to Mitigate the Wallacean Shortfall in a Megadiverse Snake Fauna - Nogueira, Cristiano C.; Argôlo, Antonio J.S.; Arzamendia, Vanesa; Azevedo, Josué A.; Barbo, Fausto E.; Bérnils, Renato S.; Bolochio, Bruna E.; Borges-Martins, Marcio; Brasil-Godinho, Marcela; Braz, Henrique; Buononato, Marcus A.; Cisneros-Heredia, Diego F.; et al. (South american journal of herpetology, 2019)
Accurate and detailed species distribution maps are fundamental for documenting and interpreting biological diversity. For snakes, an ecologically diverse group of reptiles, syntheses and detailed data on distribution patterns remain scarce. We present the first comprehensive collection of detailed, voucher-based, point-locality, range maps for all described and documented Brazilian snakes, with the major aim of mitigating the Wallacean shortfall and as a contribution towards a better understanding of this rich, threatened, and poorly studied megadiverse fauna. We recorded a total of 412 snake species in Brazil on the basis of an extensive and verified point-locality database of 163,498 entries and 75,681 unique records (available here as Online Supporting Information). Our results reveal previously undocumented patterns of distribution, sampling effort, richness, and endemism levels, resulting in a more objective view of snake diversity in the Neotropics. Apart from these achievements, we understand that the most relevant and enduring contribution of the present atlas is to stimulate researchers to publish corrections, additions, and new discoveries.